Visitors looking at italian paintings in the Louvre Museum - Paris... - Sandra Soster (Wikimedia Commons, 2019)
Notice iconographique issue de Wikimedia Commons. Titre: Visitors looking at italian paintings in the Louvre Museum - Paris, France, 2019 49.
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons